Família e escola: uma importante relação no processo educativo - SANTOS, Elenisi Ribeiro dos (2021)
Addressing the theme “Family and School” in the teaching-learning process is undoubtedly a huge challenge. This work seeks to demonstrate the reality where the family and school are located. This research was carried out in the municipal education system with teachers who work in classes from 6th to 9th grade, in Rural Education in the municipality of Uruará, and also with school managers responsible for these classes. In this sense, this work aims to identify the problems faced by the school with regard to the family's performance in the teaching-learning process, this being the main question to be answered in this research. It is a qualitative research which will be structured in the form of a case study, through an interview containing a questionnaire that was sent to duly selected professionals, who work in the municipal school system. This interview is based on renowned authors on the subject. The research “Family and School: An important relationship in the teaching process” is an important contribution to the theme, which in turn is so comprehensive and that with each passing day it undergoes modifications, according to the reality in which it has been addressed.